A Smoking Prevention Program for Aboriginal Youth - McKennitt, Daniel (First Peoples Child & Family Review, 2007)
In recent years, policymakers and medical experts have expressed alarm about the growing problem of tobacco related deaths, most speciﬁcally from smoking cigarettes. Even more alarming is the rate of tobacco use among Aboriginal people and speciﬁcally Aboriginal youth. This paper explores how a holistic approach coupled with Aboriginal healthcare professionals is necessary for an effective smoking prevention program. Moreover, recommendations are provided based on this information to help devise an effective smoking prevention program encompassing all four aspects of health; mental, physical, emotional and spiritual.